2017
DOI: 10.1007/s13730-017-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerulosclerosis associated with cutaneous and systemic plasmacytosis

Abstract: Cutaneous and systemic plasmacytosis (CSP) is a rare lymphoproliferative disorder that mainly affects middle-aged Asian individuals. Although Castleman disease is often complicated with various renal involvements, glomerulonephritis associated with CSP, which is considered as a variant of Castleman disease, is rare. This report presents the case of a 41-year-old Japanese man with nephrotic syndrome associated with CSP. Renal biopsy findings showed focal segmental glomerulosclerosis (FSGS) and diffusely mild se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Thus, it is possible to infer that DOX causes in ammation, with a possible in ltration of macrophages, which in our study can be represented by elevated index of in ammatory cells in renal tissues. These cells are responsible to increase of IL-6 mRNA expression that is frequently observed in patients with primary FSGS associated with cutaneous and systemic plasmacytosis [42], beyond other nephropathies, such as IgA nephropathy [43]. In line with this, it was also detected signi cant differences in IL-6 receptor gene (IL-6R) expression between the DOX-injected and STATTIC-treated animals.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, it is possible to infer that DOX causes in ammation, with a possible in ltration of macrophages, which in our study can be represented by elevated index of in ammatory cells in renal tissues. These cells are responsible to increase of IL-6 mRNA expression that is frequently observed in patients with primary FSGS associated with cutaneous and systemic plasmacytosis [42], beyond other nephropathies, such as IgA nephropathy [43]. In line with this, it was also detected signi cant differences in IL-6 receptor gene (IL-6R) expression between the DOX-injected and STATTIC-treated animals.…”
Section: Discussionsupporting
confidence: 55%
“…Immunohistochemically staining of human kidney biopsy specimens indicated that the expression of cathepsin D was signi cantly increased in Minimal change disease compared to that in FSGS maybe because of a high level of autophagic activity 38,39 . IL6 was demonstrated to contribute to renal diseases like FSGS 40 . Cathepsin L and IL6 were undetectable or in normal range in in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we do not believe that CLCF1 is specific for recurrent FSGS and most likely was not the Immunohistochemically staining of human kidney biopsy specimens indicated that the expression of cathepsin D was significantly increased in Minimal change disease compared to that in FSGS maybe because of a high level of autophagic activity 40,41 . IL6 was demonstrated to contribute to renal diseases like FSGS 42 . Cathepsin L and IL6 were undetectable or in normal range in our patient.…”
Section: Discussionmentioning
confidence: 99%